Aplicación web para incentivar el aprendizaje de fundamentos de programación de estudiantes de educación básica media-superior - Aviles Chalaco , Diana Stefania (2024)
Programming has become an essential skill that not only promotes technical careers but also enhances logical thinking and problem-solving skills in various fields. Despite its importance, teaching programming to new learners has its challenges, especially when it comes to maintaining their interest in the concepts being explained. To address these issues, a web application in the form of a serious game is proposed, designed to make learning programming more entertaining and educational for upper-middle basic education students. Interviews were conducted with students and teachers to determine the features of the game. In addition, prototypes were created and tested with representative users using a participatory design approach. Finally, a testing phase was carried out to evaluate the usability of the application. The results suggest that the application has the potential to increase motivation for learning programming, laying a solid foundation for future research and advancements in the field of technological education.